Photovoltaic module and photovoltaic board support piece thereof - LAI LIANGXING; ZHANG RUIJUAN; ZHENG DAILI; ZENG HONGMING; ZHANG PINGKUAN; LIN CHENWEI; HUANG MINGYUAN (2015)
The utility model discloses a photovoltaic module and photovoltaic board support piece thereof. The photovoltaic module contains photovoltaic board and photovoltaic board support piece. Photovoltaic board support piece contains a supporting beam and the board of adhereing. Supporting beam has one and puts the beams in place the body, the underbeam body and at least one lock and attach the structure. The lock attaches the structure and is located to put the beams in place between the body and the underbeam body. The upper beam body, lock attach the structure and arrange along an array orientation with the underbeam body. The board of adhereing is the one side that sets up in the underbeam body, and the board of adhereing has the face of adhereing. The face of adhereing is perpendicular to array orientation. The center that the lock attaches the structure defines height with the face of adhereing along array orientation. The optional position of the opposite side of board of adhereing relatively of the underbeam body is less than or equal to height down to locking the distance of attaching the center of structure.